1953
DOI: 10.1139/v53-133
|View full text |Cite
|
Sign up to set email alerts
|

The Electrical Conductivity of Molten Oxides

Abstract: Electrical conductivities of some molten oxides have been determined. In order of decreasing equivalent conductances a t their melting points the oxides investigated were: LitO, I'bO, TeO?, Moo?, BitO3, V?Os, Sb,Oa, an! CrOS. The variation of the observed values of the s~e c~f i c conduct~vities. K. w~t h the absolute tern-, , perature, T, can be described b; an equation of the form,where A , B, C , etc. are constants. While the experimental data are adequately described by an equation of this form containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

1967
1967
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(28 citation statements)
references
References 1 publication
1
27
0
Order By: Relevance
“…We have no data on the high‐temperature electrical conductivity of the 5 at.% Yb 3+ doped (La 0.1 Y 0.9 ) 2 O 3 composition. However, it should be noted that the obtained values are slightly less than the conductivity of pure Y 2 O 3 above the melting point, which equals 0.9 (Ω·cm) −1 …”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…We have no data on the high‐temperature electrical conductivity of the 5 at.% Yb 3+ doped (La 0.1 Y 0.9 ) 2 O 3 composition. However, it should be noted that the obtained values are slightly less than the conductivity of pure Y 2 O 3 above the melting point, which equals 0.9 (Ω·cm) −1 …”
Section: Resultsmentioning
confidence: 65%
“…However, it should be noted that the obtained values are slightly less than the conductivity of pure Y 2 O 3 above the melting point, which equals 0.9 (ΩÁcm) À1 . 30 An SEM study of the surfaces of a sample microwave heated at a rate of 200°C/min to 1500°C has revealed that the surface relief is uneven on the grain size scale (Fig. 6, a).…”
Section: Resultsmentioning
confidence: 99%
“…Assessment of Al 2 O 3 conductivity.-Previous efforts to measure the electrical conductivity of Al 2 O 3 (l) are numerous, 21,[56][57][58][59][60][61][62][63] which is uncommon for refractory melts. Although recent researchers have compared their results with a partial selection of previous efforts, the last complete review of Al 2 O 3 (l) conductivity is that of Shpil'rain et al 60 More recent reviews, e.g., 67 have omitted without justification contributions from the aerodynamic levitation method.…”
Section: Appendix Cmentioning
confidence: 99%
“…A summary of previous measurements and the results of this assessment in the temperature range range T m (Al 2 O 3 ) = 2327 K 64,65 to T m (Ir) = 2719 K 65,66 are presented in Figure C1. Van Arkel et al 56 were the first to report the conductivity of Al 2 O 3 (l). Their estimate, 15 S cm −1 , was derived indirectly from the performance of an electric arc above Al 2 O 3 (l)…”
Section: Appendix Cmentioning
confidence: 99%
“…The high-temperature electric conductivity of the 5 at % Yb 3+ doped (La 0.1 Y 0.9 ) 2 O 3 composition is not known. However, it should be noted that the estimated values are slightly lower than the conductivity of pure Y 2 O 3 above the melting point, which equals 0.9 (Ω·cm) −1 [46]. …”
Section: Resultsmentioning
confidence: 99%